Identification of Types of Fish Captured by Fishermen at TPI Wuryantoro Wonogiri that are Consumed by the Community - Tri Wiharti; Nur Rokhimah Hanik (Jurnal Biologi Tropis, 2022)
Research with the title “Identification of Types of Fish Captured by fishermen at TPI Wuryantoro Wonogiri that are consumed by the community”.The aims of this study are: to identify the types of fish caught by fishermen at TPI Wuryantoro that are consumed by the community as student learning materials in the Vertebrate Animal Systematic Course, Biology Education Study Program, Faculty of Teacher Training and Education, Veterans University Bangun Nusantara Sukoharjo in 2021. In In this study, fish sampling was carried out at the Wuryantoro fish auction, Gajah Mungkur Wonogiri reservoir, while identification was carried out in the laboratory of the Biology Education Study Program, FKIP Univet Bantara Sukoharjo. The results of the identification of the types of fish caught by fishermen at TPI Wuryantoro, Gajah Mungkur Wonogiri reservoir. There are 7 types of fish, of which 7 species of fish were found to be in 1 class, namely the Ostheichthyes class, included in 2 sub-classes, namely the Teleostei and acthynopterigii subclasses, included in 4 orders, and 7 families. The fish are: red snapper (Lutjanus argntimaculatus), catfish (Clarias batrachus), tilapia (Oreochromis niloticus), Tawes Fish (Barbonymus gonionotus), betutu fish (Oxyeleotris marmorat), cursed fish / cork (Channa striata), catfish (Pangasius hypophthalmus). Fisherman's catch at TPI Wuryantoro Gajah Mungkur Wonogiri reservoir, can be used as study material for students of the Vertebrate Animal Systematic course.